High-Performance Liquid Chromatographic Analysis of the 2-Chloroprocaine Metabolite, Diethylaminoethanol, in Blood and Serum. Issue 3 (1st May 1999) - Meng, Qing C.; Kramer, Thomas H.; D., Pharm.; Arthur, G. Richard; Kim, Philip S.; Ferrante, F. Michael
Abstract : Background and Objectives: 2-Chloroprocaine is rapidly metabolized in the blood to yield 2-chloro-para-aminobenzoic acid (an inactive metabolite) and diethylaminoethanol (DEAE). DEAE possesses local anesthetic activity. The only reported assay for DEAE is a colorimetric method. Methods: Clinical samples of whole blood and serum were obtained from patients receiving stepped intravenous infusions of 3% 2-chloroprocaine. A high pH-dependent liquid-liquid extraction step with diethyl ether was used to eliminate interfering peaks in high-pressure liquid chromatography (HPLC) analysis. Separation and quantitation were performed using HPLC on a polymeric-reversed phase column with a mobile phase consisting of 10% or 20% acetonitrile (for whole blood or serum analysis, respectively) in 50 mm aqueous sodium phosphate buffer, pH = 11.50. The elution order of DEAE and its analogues was tested to interpret the HPLC separation mechanism. Results: Extraction recovery of DEAE from whole blood was 67 ± 13.5%, from serum, 71 ± 12.2%, and from water, 75 ± 2.9%. The high pH value of the mobile phase resulted in sharp, well-resolved peaks with run times of approximately 8 minutes using 20% acetonitrile. The lower limit of detection was 5 ng/mL of DEAE from a 1-mL sample. The elution order of DEAE and its analogues indicated that separation was based on the hydrophobicity of the analytes rather than polar group interactions occurring with silica-based stationary phase. Conclusions: A new, simple and rapid HPLC method for extraction and measurement of DEAE in whole blood or serum samples is reported here.